(untitled) (Research, Society and Development, 2022)
Introduction: Malaria is a public health problem, due to its high incidence in the world, with high rates of morbidity and mortality, whose consequences associated with the disease can expressively influence the development of countries, states and regions, in addition to the risk for the quality of individuals’ lives. Objective: To outline the epidemiological picture of the malaria outbreak in the Areinha mining in the health micro-region of a municipality in Minas Gerais, Alto Vale do Jequitinhonha, Minas Gerais (Brazil). Method: Epidemiological, descriptive reported cases of malaria in the Notifiable Diseases Information System. For analysis, the SPSS Statistics program (version 20.0) was used. Results: There were 23 cases of autochthonous malaria, 86.95% in men, mean age 33 years and 56.52% with incomplete primary education. The mining activity was the determining factor for the acquisition of the disease, 82.61%. The general symptoms presented were: fever, general malaise and chills. The infecting species was P. vivax at 100%, and the treatment adopted was the long regimen recommended by the Ministry of Health. Conclusion: The results show the importance of surveillance in the care of individuals coming from the mining area, so those confirmed cases of malaria can receive specific treatment, as well as provide subsidies for monitoring actions and new studies that can help to reduce cases of malaria. malaria in mining areas.